2011
DOI: 10.1063/1.3623485
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional model of the programming kinetics of conductive-bridge memory cells

Abstract: A one-dimensional model of filament growth in conductive-bridge memory cells is presented, in which ions are thermally excited from the anode surface into the electrolyte, pulled by the electric field through a periodic series of wells and reduced at the cathode to form a metallic filament. The voltage, temperature, and thickness dependencies of the time required to program a cell are calculated, and material parameters for Ag/GeS2/W cells are obtained by comparison to experiment. The relation of the model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 4 publications
5
48
0
Order By: Relevance
“…The exponential relation has been explained by the migration of Cu þ ions, the redox reaction on the electrode, and the nucleation of Cu atoms. [10][11][12] In the following, the volatile switching behavior has been characterized and compared with nonvolatile switching. The SET voltages at different voltage ramp rates are shown in Fig.…”
Section: -2mentioning
confidence: 99%
“…The exponential relation has been explained by the migration of Cu þ ions, the redox reaction on the electrode, and the nucleation of Cu atoms. [10][11][12] In the following, the volatile switching behavior has been characterized and compared with nonvolatile switching. The SET voltages at different voltage ramp rates are shown in Fig.…”
Section: -2mentioning
confidence: 99%
“…[20] However, only a few results have been published so far to study resistive switching on a microscopic scale. [21,22,23,24,25] All the investigations are mainly focusing on initial filament growth rather than on complete formation and dissolutions cycles. Recently, Menzel et al reported on results from two-dimensional kinetic MonteCarlo simulations which allow for several leading physical and chemical processes underlying resistive switching in electrochemical metallization cells.…”
Section: Simulation Approachmentioning
confidence: 99%
“…[21,22,23,24,25,26] Particularly, the redox reactions at the electrodes are important. The related rates of oxidation of metal atoms and reduction of metal ions are assumed to be constants weighted by Arrhenius-like probabilities which depend on the local electric field and therefore on the local potential.…”
Section: Simulation Approachmentioning
confidence: 99%
“…switching time (equivalent to the Faradaic reaction rate), the activation energies and the current-time (I-t) relaxation it has been shown that the formation of the critical nucleus is rate limiting and not the electron charge transfer or the diffusion/hopping within this system. Despite various simulation models on the switching kinetics 37,45,46 a complete theoretical model covering all limiting factors is yet missing.…”
Section: Introductionmentioning
confidence: 99%